2020
DOI: 10.3390/agronomy11010073
|View full text |Cite
|
Sign up to set email alerts
|

The Elucidation of Total Polyphenols, Individual Phenolic Compounds, Antioxidant Activity of Three Underutilized Fruit Species—Black Crowberry, Honeyberry, European Cranberry with Their Accumulation

Abstract: Total polyphenols content (TPC), antioxidant activity (AA) and polyphenolic spectrum assay of three underutilized fruit species—black crowberry (Empetrum nigrum), honeyberry (Lonicera kamtschatica) and European cranberry (Vaccinium oxycoccos) is the aim of the present work. TPC and AA assay was performed by spectrophotometry and “individual phenolic compounds” were established by high-performance liquid chromatography. The results showed that TPC ranged from 1.61 ± 0.16 (European cranberry) up to 5.65 ± 0.01 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 62 publications
2
6
0
Order By: Relevance
“…Different studies have demonstrated that phenolic compounds significantly increase the antioxidant capacity of natural products. [42] This behavior was observed in the present study, with a correlation found between high phenolic concentration and high antioxidant capacity. Correlation analyses showed high values between phenolic compounds and antioxidant capacity (DPPH, ABTS, ORAC and FRAP) of extracts (r = 0.98 in all cases, Figure 3) and flower fractions (0.97 to 0.99, Figure 4).…”
Section: Antioxidant Activitysupporting
confidence: 84%
“…Different studies have demonstrated that phenolic compounds significantly increase the antioxidant capacity of natural products. [42] This behavior was observed in the present study, with a correlation found between high phenolic concentration and high antioxidant capacity. Correlation analyses showed high values between phenolic compounds and antioxidant capacity (DPPH, ABTS, ORAC and FRAP) of extracts (r = 0.98 in all cases, Figure 3) and flower fractions (0.97 to 0.99, Figure 4).…”
Section: Antioxidant Activitysupporting
confidence: 84%
“…The filtrates were combined and diluted with 80% ethanol to 100 mL, and the obtained extract was used for the determination. The quantification fruit phenolics was determined by the Folin–Ciocalteu method [ 25 ], with some modifications. An total of 1 mL of extract with 20 mL of deionized water and 1 mL of Folin–Ciocalteu’s reagent was mixed.…”
Section: Methodsmentioning
confidence: 99%
“…The GA content in the initial solution, cryoconcentration samples, and beads was quantified by the Folin-Ciocalteu assay [32], with slight modifications. Specifically, 100 µL of solution was mixed with 7900 µL of deionized water, and then, 500 µL of Folin-Ciocalteu reagent was added.…”
Section: Ga Contentmentioning
confidence: 99%